Performance of The 3 Blades Horizontal Savonius Water Wheel With Variation of Angle Deflector - Wibowo, Daniel; Wihadi, Dwiseno; Martanto, Martanto; Tjendro, Tjendro; A, Ronny (SENATIK STT Adisutjipto, 2019)
In Indonesia the needs toward energy has been increasing. Therefore, eco-friendly renewable energy becomes an alternative power source. In relation to the idea, within the conduct of the experimental study the researcher designed a Savonius-type waterwheel with horizontal axis and the waterwheel was tested in the river stream. Then, within the design the researcher applied one waterflow regulator with the angle variation 30˚, 45˚ and 60˚. The study was conducted on river flow with a flow velocity of ± 0.6 m / s. the result is the addition of the deflector angle affects the ability to support the load, the maximum wheel efficiency(Cp) of 0.57.